Application of generalized linear models in the modeling of dairy production in Agreste Meridional Pernambuco (Research, Society and Development, 2020)
The article aimed to assess the factors that may influence the production of cow's milk in the municipalities that are part of the Agreste Meridional region of Pernambuco. Initially, an exploratory analysis of the variables was carried out in order to observe some measures of position and dispersion. Then, the class of Generalized Linear Models was used to assess how the variables influence milk production. As a dependent variable the production of cow's milk was considered and the explanatory variables were the precipitation that occurred in the municipalities in 2018, corn production, production of forage palm, the presence of a cooperative / association in the municipalities and the number of enterprises participating in the family farming. The results found showed that in 2012, a year of extreme drought, the average milk production fell by 36% in the region. In addition, it was found that the number of establishments that produce milk and participate in family farming were responsible for 61% of the average milk production in Agreste Meridional. Municipalities that have milk production cooperatives and / or associations had higher average production than municipalities that did not have cooperatives and / or associations.